Neuroprotective mechanism of Loranthus parasiticus (L.) merr against oxidative stress-induced damage in NG108-15 cells / Daniel Wong Zin Hua - Wong, Daniel Zin Hua (2012)
Oxidative stress-induced neurodegenerative diseases have become more prevalent lately due to the stressful environment and lifestyle. Growing empirical scientific evidences which support the use of plant-derived antioxidants in the control of neurodegenerative disorders has been validated in the present investigation. Loranthus parasiticus (L.) Merr, a chinese traditional folk medicine which has been used in treating brain diseases was selected for the present study. Therefore, L. parasiticus was hypothesized to exhibit antioxidative and neuroprotective properties in NG108-15 neuroprotection model. Loranthus parasiticus aqueous fraction (LPAF) which showed the highest antioxidative and neuroprotective activities against H2O2 among the tested extract and fractions was subjected to a bioassay-guided fractionation and isolation approach to identify the most potent neuroprotective compound. (+)-Catechin was found to be the most potent neuroprotective compound and its underlying mechanisms were evaluated subsequently. (+)-Catechin significantly reduced reactive oxygen species production, phosphatidylserine externalization, mitochondrial membrane potential depolarization, sub-G1 apoptotic fraction induction, and increased the percentage of cell viability following H2O2-induced oxidative stress insult. Moreover, (+)-catechin increased the H2O2-induced reduction of SOD and GPx activities. (+)-Catechin also upregulated Bcl-2 and downregulated Bax, resulting in a decreased ratio of Bax/Bcl-2. Interestingly, oxidative stress-induced overexpression of chemokine CCL21 was significantly attenuated by (+)-catechin, indicating a novel role of (+)-catechin in neuroprotection context via the regulation of neuronal chemokine CCL21. Collectively, the present findings have proven our hypothesis and support the use of L. parasiticus in managing oxidative stress related neurodegenerative diseases.